2000
DOI: 10.1038/sj.onc.1203582
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal common domain of simian virus 40 large T and small t antigens acts as a transformation suppressor of the HER-2/neu oncogene

Abstract: Overexpression of HER-2/neu (also known as c-erbB-2) proto-oncogene frequently occurs in many di erent types of human cancers, including ovarian carcinoma, and is known to enhance tumor metastasis and chemoresistance. Previous studies showed that inhibition of HER-2/neu expression by various agents, such as adenovirus E1A and simian virus 40 large T, can lead to suppression of tumorigenicity of HER-2/neu-overexpressing cancer cells. Here we report that T/t-common, which contains the N-terminal common domain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…9,27,28 Previously, we reported that SV40 T/t-common polypeptide, which contains the Nterminal common domain of SV40 large T and small t antigens, has transcriptional repression activity 29 and can specifically inhibit HER2 expression in the HER2-overexpressing ovarian carcinoma cells. 30 These results suggest that T/t-common might have the ability to inhibit angiogenesis and tumor growth in HER2-overexpressing ovarian cancer. Here we report that T/t-common can inhibit the ability of HER2-overexpressing human ovarian cancer cells to induce angiogenesis.…”
Section: Introductionmentioning
confidence: 83%
“…9,27,28 Previously, we reported that SV40 T/t-common polypeptide, which contains the Nterminal common domain of SV40 large T and small t antigens, has transcriptional repression activity 29 and can specifically inhibit HER2 expression in the HER2-overexpressing ovarian carcinoma cells. 30 These results suggest that T/t-common might have the ability to inhibit angiogenesis and tumor growth in HER2-overexpressing ovarian cancer. Here we report that T/t-common can inhibit the ability of HER2-overexpressing human ovarian cancer cells to induce angiogenesis.…”
Section: Introductionmentioning
confidence: 83%
“…Plasmids pRSV.3-BglII, pRSV-T/t-common, pCMVHER2WT, pcDNA3, pCMV-bcl2, and pCMV-1 were previously described (25,31). The plasmid pCMV-T/t-common was constructed by inserting the HindIII-XbaI fragment of pRSV-T/t-common, which contains T/t-common coding unit, into the corresponding sites of pcDNA3.1 (purchased from Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…We also reported that T/t-common, through inhibition of HER2/neu, can suppress the tumorigenic potential of the HER2/ neu-overexpressing ovarian cancer cells (25). T/t-common has been shown to have strong transcriptional repressing activity (26) and express a biological activity equivalent to the NH 2 -terminal nonconserved domain and the conserved domain 1 of E1A (27).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations